Analisis Strategi Jaringan Bisnis, Pemasaran dan Produksi Pada Produk Roll Cake “On a Roll” - Resya Dwi Marselina; Amanda Cahya Nilamsari; Asep Nurjaman; Dede Nurhasanah; Farhan Nur Jamal; Ilham Sandi Ferdiana (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research is motivated by an analysis of business networks, marketing and production in the business world which creates very tight competition. To respond to this, the author conducted business network analysis research, marketing and production carried out by the UMKM Roll Cake "On a Roll". The objectives that must be achieved in this research include: (1) to find out what products are produced by Roll Cake "On a Roll" (2) To find out which business networks are suitable for Roll Cake "On a Roll" products, (3 ) to find out the production process of Roll Cake "On a Roll", (4) to find out how the marketing process of Roll Cake "On a Roll", (5) to find out the financial reports of the Roll Cake "On a Roll" business. This research was conducted directly with the founder of Roll Cake "On a Roll". This research looks for business networks, marketing processes and production processes carried out by Roll Cake "On a Roll" entrepreneurs to make decisions regarding the development carried out from the product being marketed to the hands of consumers. This research uses qualitative methods, namely interviewing Roll Cake "On a Roll" entrepreneurs regarding business networks, marketing, production, sales and financial reports carried out to gain profits.